2005
DOI: 10.1242/jcs.01586
|View full text |Cite
|
Sign up to set email alerts
|

Cortactin regulates cell migration through activation of N-WASP

Abstract: Cortactin is an actin-associated scaffolding protein that regulates cell migration. Amplification of the human gene, EMS1, has been detected in breast, head and neck tumors, where it correlates with increased invasiveness. Cortactin can regulate actin dynamics directly via its N-terminal half, which can bind and activate the Arp2/3 complex. The C-terminal portion of cortactin, however, is thought to have limited function in its regulation of the actin polymerization machinery. In this report, we identify a rol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
128
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(137 citation statements)
references
References 49 publications
(51 reference statements)
8
128
1
Order By: Relevance
“…Effects of Arg on Branch Formation by Arp2/3 ComplexCortactin weakly activates branch formation by the Arp2/3 complex on its own, but it robustly stimulates branch formation when combined with the nucleation-promoting factor N-WASp (9,(35)(36)(37). We confirmed that 1 M cortactin increased branching by Arp2/3 complex and N-WASp GST-VCA ϳ3-fold (Fig.…”
Section: Resultssupporting
confidence: 78%
“…Effects of Arg on Branch Formation by Arp2/3 ComplexCortactin weakly activates branch formation by the Arp2/3 complex on its own, but it robustly stimulates branch formation when combined with the nucleation-promoting factor N-WASp (9,(35)(36)(37). We confirmed that 1 M cortactin increased branching by Arp2/3 complex and N-WASp GST-VCA ϳ3-fold (Fig.…”
Section: Resultssupporting
confidence: 78%
“…p120-catenin has emerged as a master regulator of VE-cadherin stability as it prevents VE-cadherin endocytosis by clathrin-coated adaptor AP1 (17,37,39) and restricts RhoA activity (40,41). A recent study showed that in fibroblasts, p120-catenin also induces the activation of cortactin, a well known partner of N-WASP (42), to induce lamellipodia formation for their migratory events (33). We ruled out the role of p120-catenin as the activator of N-WASP because knockdown of p120-catenin had no effect on N-WASP activity or the interaction of N-WASP with Arp2 and actin.…”
Section: Discussionmentioning
confidence: 92%
“…79,80,83,85,99,100 Furthermore, cortactin has multiple functions in cell motility and is able to activate N-WASP. 101 For further readings to cortactin, please see recent reviews. [102][103][104][105] Both WASP and cortactin are targeted and activated by a number of cellular signals.…”
Section: The Arp2/3 Complex a Central Player In Junction Dynamics Ofmentioning
confidence: 99%